An Accessible and Affordable Transport Intervention for Older People Living in the Community. Issue 2 (May 2018) - Lee, Elinda Ai Lim; Same, Anne; McNamara, Beverley; Rosenwax, Lorna
The ability to remain mobile is linked to the independence, health, and well-being of older people, but studies are needed to confirm the impact of community transport services. This study investigated the need for, and the impact of, a transport intervention on the independence and well-being of older people living in an Australian urban community. Using qualitative and quantitative data collected from pre-intervention ( n = 32) and post-intervention interviews ( n = 11), the need and impact of a community transport service were examined. The results of the study indicate investment in community transport has the potential to positively affect the lives of older people. Accessible affordable transport for older people signals an age-friendly society that values participation of all members of society, regardless of age.